Constricted, lame and pro-cyclical : Fiscal policy in the euro area revisited - Deroose, Servaas; Larch, Martin; Schaechter, Andrea; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : Office for Infrastructures and Logistics in Brussels, 2008)
It is often argued that fiscal stabilisation in the euro area compares unfavourably with the US, not least because of the perceived limitations of the Stability and Growth Pact. This paper qualifies this perception by taking a closer look at fiscal policy making since the mid-1990s. It examines a number of elements which are generally overlooked or not considered in the analysis of fiscal stabilisation. In particular, on top of discretionary fiscal policy, which generally is at the core of existing studies, it also takes into account the size of automatic stabilisers. Moreover, it considers the difference between policy intentions, as formulated or perceived in real time, and actual outturns, and possible reasons for the gap between the two. On the basis of such a more comprehensive analysis, fiscal stabilisation in the euro area appears less dire than commonly assumed. It also suggests a number of points on how to improve the track record, including by strengthening fiscal governance.
Economic Papers.